Sosialisasi Pengolahan Limbah Sekam Padi Menjadi Bahan Bakar Alternatif pada IKM Penggilingan Padi - Dwi Setyorini; Achmad Qodim Syafaatullah; Muh Setiawan Sukardin; Enni Sulfiana; Iman Pradana A. Assagaf; Angger Bagus Prasetiyo (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
Waste is a by-product that is produced in almost all industries, as well as in rice milling SMEs. The waste produced by IKM calling rice is rice husk. At this time rice husk waste is only sold at very cheap prices to other IKM. Whereas rice husk can be processed into various products, one of which is briquettes as an alternative fuel from biomass. Where briquettes are quite in demand by some people so that the selling price is also higher and the method of manufacture is quite easy. Therefore, the purpose of this community service is to provide socialization regarding the use of rice husk as an alternative fuel. The activity was carried out at rice milling IKM in Gowa district, with a total of 17 participants. Activities are divided into four stages including planning, preparation, implementation and evaluation. Planning and preparation is carried out with site surveys and interviews with partners regarding any problems encountered. At the implementation stage, participants received material exposure regarding the dangers of waste utilization and procedures for processing rice husks into briquettes, and submitted briquettes that had previously been made on campus as a reference. Furthermore, the evaluation stage is carried out through filling out questionnaires which are distributed during the implementation process. The target of carrying out this activity is that partners know the process of processing rice husk waste into a product that has high selling value in the form of briquettes.